Bereaved Families' Experiences of End-of-Life Care at Home for Older Adults with Non-Cancer in South Korea. Issue 1 (2nd January 2019) - Lee, Hanul; Lee, Jiwon; Lee, Jong-Eun
ABSTRACT: The aim of this study was to gain an understanding of the experiences of families who care for older adults with non-cancer diseases at the end of their lives. The data accrued through in-depth interviews, analyzed using Giorgi's phenomenological method: caregiving burden; situational responsibility; consolation by support; and mourning for the deceased. In Korean culture, adult children had the responsibility of caring for their aged parents as a burden of caregiving and as a main motive for caregiving. Educational and psychological support programs for caregivers should aim to boost confidence, rather than merely focusing on their burden.